Impulse generation and initial velocity differences in two-foot running jumps with and without a basketball - Liu, J. M.; Zaferiou, A. (ISBS Proceedings Archive (Michigan), 2023)
This study aimed to (1) identify the roles of each leg in impulse generation and (2) determine differences in impulse generation and initial centre of mass velocities in two-foot running jumps with and without a ball. Eight recreational to collegiate basketball players performed three to ten repetitions of two-foot running jumps with and without a ball. We found that the first leg generated more backward and vertical impulse than the second leg in both two-foot running jumps with and without a basketball. Two-foot running jumps with a ball resulted in lower jump height and less vertical impulse generated by the second leg vs. jumps without a ball. These different impulse generation strategies and jump heights when jumping with a ball prompt further research to uncover why there are differences and which training practices can address the differences and lead to higher jump heights with a ball.